The Datafied Society Studying Culture through Data - Schäfer, Mirko Tobias; van Es, Karin (Amsterdam University Press, 2017)
As machine-readable data comes to play an increasingly important role in everyday life, researchers find themselves with rich resources for studying society. The novel methods and tools needed to work with such data require not only new knowledge and skills, but also a new way of thinking about best research practices. This book critically reflects on the role and usefulness of big data, challenging overly optimistic expectations about what such information can reveal, introducing practices and methods for its analysis and visualisation, and raising important political and ethical questions regarding its collection, handling, and presentation.